2016
DOI: 10.1016/j.kint.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23 directly targets hepatocytes to promote inflammation in chronic kidney disease

Abstract: Patients with chronic kidney disease (CKD) develop increased levels of the phosphate-regulating hormone, fibroblast growth factor (FGF) 23, that are associated with a higher risk of mortality. Increases in inflammatory markers are another common feature of CKD that predict poor clinical outcomes. Elevated FGF23 is associated with higher circulating levels of inflammatory cytokines in CKD, which can stimulate osteocyte production of FGF23. Here, we studied whether FGF23 can directly stimulate hepatic production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
284
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(296 citation statements)
references
References 73 publications
11
284
1
Order By: Relevance
“…1 In the current issue of the journal, Singh et al (2016) 2 implicates fibroblast growth factor 23 (FGF23) as an additional, novel factor contributing to uremic inflammation. Although higher FGF23 levels have been independently associated with higher levels of inflammatory markers in CKD patients, 3 in the current article, Singh et al 2 demonstrate through a series of elegant in vitro and in vivo experiments that FGF23 directly induces hepatic expression and secretion of inflammatory cytokines.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 In the current issue of the journal, Singh et al (2016) 2 implicates fibroblast growth factor 23 (FGF23) as an additional, novel factor contributing to uremic inflammation. Although higher FGF23 levels have been independently associated with higher levels of inflammatory markers in CKD patients, 3 in the current article, Singh et al 2 demonstrate through a series of elegant in vitro and in vivo experiments that FGF23 directly induces hepatic expression and secretion of inflammatory cytokines.…”
mentioning
confidence: 99%
“…Lastly, in the 5/6 nephrectomy rat model, Singh et al 2 characterized the effects of pharmacologic blockade of FGF23-FGFR4 signaling. Compared with control animals, 5/6 nephrectomized rats had elevated FGF23 levels, increased hepatic CRP expression, and increased serum CRP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent experimental data demonstrated that inflammation directly stimulates FGF-23 transcription and protein expression in osteocyte cell lines and increases circulating FGF-23 levels in animals with and without CKD in part through a hypoxia-inducible factor 1 a-depending mechanism. Conversely, elevated FGF-23 was found to induce hepatic production of IL-6 and CRP through an FGFR4-dependent but Klotho-independent mechanism [61,62]. Overall, the results of the above studies suggest the presence of a positive feedback loop between inflammation and elevated FGF-23 levels in CKD.…”
Section: Fibroblast Growth Factor-23 and Other Ckd-related Cardiovascmentioning
confidence: 75%
“…FGF23 acts through triggering genes, which encode cytokines such as interleukin (IL)-6 and tumor necrosis factor-alpha (TNF-α) [15,16] and associations of FGF23 levels with pro-inflammatory markers have been described in both CKD and non-CKD cohorts. This highlights the role of FGF23 as an inflammatory mediator, presumably acting through cytokine upregulation [9,[17][18][19][20][21]. Interestingly, a recent study described that FGF23 exposure inhibits neutrophil recruitment through interference of integrin expression, compromising host defense in CKD [22].…”
Section: Introductionmentioning
confidence: 93%